Diet and feeding strategy of the forkbeard Phycis phycis (Pisces: Phycidae) from the Portuguese continental coast. (19th July 2017) - Silva, Ana Rita; Vieira, Ana Rita; Sequeira, Vera; Paiva, Rafaela Barros; Gordo, Leonel Serrano; Neves, Ana
Abstract : The diet and feeding behaviour of the forkbeard Phycis phycis was studied based on 246 stomachs collected between May 2011 and April 2012 from a commercial fleet operating off the central west coast of Portugal. A total of 44 prey items were identified in the stomachs which were merged into major groups to avoid problems with low expected frequencies. The following taxonomic categories were considered: non-decapod Crustacea, Caridea, Anomura, Munida spp., Processa spp., Brachyura, Pisces, Trisopterus luscus . In order to investigate possible diet differences between fish size classes, a cluster analysis was performed using the mean abundance of each prey group by forkbeard 5 cm length class, and three length groups (LG) were obtained: <22.5, 27.5–37.5 and >42.5 cm. Seasonally, Caridea was the main prey group during winter and autumn while Pisces was predominant during the rest of the year. Caridea was the most important prey group for LG1 and LG2 while in LG3 Pisces was the principal one. The forkbeard feeding behaviour may be characterized as presenting a shift pattern from a more generalist diet (small Crustacea, mainly Caridea) in the young adults to a more specialist strategy (teleosts) in the adults.